THE LIABILITY OF PUBLIC SERVANTS - Diana-Mihaela Malinche (Perspectives of Law and Public Administration, 2018)
The data presented in this study was collected by using the content analysis as a research method, starting from the theoretical and practical concepts of administrative law as well as from national legislative regulations adopted with the purpose of delimiting the notion of public office and perceiving the civil servant, through the specifics of the civil service, as a link between the public administration and the served community. The civil servant is the person legally and morally invested with the exercise of the competence of a public authority or institution as a result of the performance of a public office and the exercise of public authority. Starting from the specifics of the public function and the way in which the professional activity of the civil servants is regulated, in the content of this paper I will detail the types of responsibility that precede the public function. Violation of service duties by civil servants attract disciplinary, contraventional, civil or criminal liability, depending on the case. Therefore, the specificity of the deviations is precisely the fact that the deviations can occur during the exercise of the public function, in violation of the norms of conduct influencing the public image of the official, as well as any other actions related to the service relations of the civil servant. By the nature of the occupied position, the civil servant becomes an example of morality, legality and transparency for the members of the community.